1973
DOI: 10.1002/pssb.2220570129
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic chemical shift of nuclear magnetic resonance in single crystals of tellurium and selenium

Abstract: The anisotropies of the chemical shifts in tellurium and selenium are analysed theoretically. It is shown that the second order paramagnetic chemical shift gives the main contribution t o the anisotropies. The anisotropy of the chemical shift is calculated assuming molecular wave functions for the valence electrons derived on the basis of Reitz's band calculation and good agreement is obtained with the observed anisotropy for tellurium. It is found in the analysis that there exists about 2% mixing of the bondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Solid-state NMR investigations of elemental selenium have demonstrated the sensitivity of 77 Se chemical shifts to minor changes in the local environment since the initial investigation of a single crystal of trigonal selenium at 77 K (Table 2) [84]. This study indicated that the most shielded principal component lies nearly parallel to the direction of the helices [84][85][86]. Subsequent variable temperature experiments up to 480 K have demonstrated a general decrease in selenium shielding with increasing temperature for crystalline selenium, see Table 2 [87][88][89].…”
Section: Seleniummentioning
confidence: 93%
“…Solid-state NMR investigations of elemental selenium have demonstrated the sensitivity of 77 Se chemical shifts to minor changes in the local environment since the initial investigation of a single crystal of trigonal selenium at 77 K (Table 2) [84]. This study indicated that the most shielded principal component lies nearly parallel to the direction of the helices [84][85][86]. Subsequent variable temperature experiments up to 480 K have demonstrated a general decrease in selenium shielding with increasing temperature for crystalline selenium, see Table 2 [87][88][89].…”
Section: Seleniummentioning
confidence: 93%
“…We estimated the angular difference to be approximately 6° by comparing the two-line spectrum with the shift parameters reported in ref. 31 . When the maximum current density of 82 A cm −2 with the pulse duration of 650 μs is applied to the sample, the temperature of the sample is estimated to have risen by 5 K at most; this estimate was obtained by calculating the product of the applied current and the voltage between the electrodes including the voltage drop due to the contact resistance.…”
Section: Methodsmentioning
confidence: 99%
“…3a, b and 5a). We estimated the angular differences between the magnetic field directions and the c axis to be approximately 7 • for Sample #1 and 9 • for Sample #2 by comparing the two-line spectrum with the shift parameters [34].…”
Section: Measuring Methodsmentioning
confidence: 99%
“…3 )tellurium [19]. The chirality of the covalent-bond helices determines the polarities of many physical properties, such as the angular-momentum texture in the k space [20][21][22], natural optical rotatory power [23][24][25][26], secondharmonic generation [27], piezoelectricity [28,29], shapes of etch pits [30], resonant diffraction with circularly polarized x rays [31,32], polarized neutron scattering [33], and NMR chemical shift [34] (see Supplemental Material [19]).…”
Section: Crystal and Electronic Structures Of Trigonal Telluriummentioning
confidence: 99%